2010
DOI: 10.1089/lap.2010.0013
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Resection of Retrocaval Paraganglioma

Abstract: To our knowledge, this is the first report of the laparoscopic resection of a retrocaval paraganglioma. For the resection of a paraganglioma, in this location, laparoscopy has the advantage of precise visualization, which helps to resect the tumor completely. Laparoscopic resection of a paraganglioma, despite the high level of compression of the IVC, is a feasible, reproducible technique with appropriate preoperative planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In some cases, complete excision is difficult due to the highly vascular nature of paragangliomas and their proximity to major blood vessels. While some authors have reported the successful resection of retrocaval paragangliomas with or without the need for vena cava reconstruction [3-6], the location of the present paraganglioma behind the retrohepatic portion of the IVC made it difficult to resect the tumor completely. A combined partial hepatectomy was performed to observe the relationship between the tumor and IVC directly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, complete excision is difficult due to the highly vascular nature of paragangliomas and their proximity to major blood vessels. While some authors have reported the successful resection of retrocaval paragangliomas with or without the need for vena cava reconstruction [3-6], the location of the present paraganglioma behind the retrohepatic portion of the IVC made it difficult to resect the tumor completely. A combined partial hepatectomy was performed to observe the relationship between the tumor and IVC directly.…”
Section: Discussionmentioning
confidence: 99%
“…Although most paragangliomas are located along the para-aortic sympathetic chains in the urinary bladder, thoracic cavity, or head and neck, they have also been found to develop in other regions of the body [2]. Resection of paragangliomas can be difficult, due to the complex anatomy and intensive intraoperative hemodynamic control needed, particularly as retrocaval paragangliomas often develop in proximity of the vena cava [3,4]. Correspondingly, meticulous surgical procedures are required for resection of these tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen of the 33 studies reported blood loss, whose median is 100 mL (10-1500 mL). Six trials 2,4,20,27,31,32 showed 162.0 -191.0 mL, <100 mL, 70 mL (10-150 mL), 20 mL (0-1000 mL), 100 -175 mL, 516 mL (390-600 mL), respectively. The data from the above studies fluctuated greatly partially because of variability in the number and course of feeding vessels and laparoscopic experience.…”
Section: Data From the Literaturementioning
confidence: 99%
“…Our surgical technique for the laparoscopic resection of retrocaval EAP has been described previously. 19 Briefly, five ports were placed transperitoneally. The tumor was exposed behind the inferior vena cava (IVC) (Fig.…”
Section: Surgical Techniquementioning
confidence: 99%